Eklesiologi dan Panggilan Gereja di Tengah Perkembangan Zaman - Exaudi Aprilia Sihite; Ririn Octaviana Ginting; Sasta Panjaitan (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
Ecclesiology and the church's calling amidst the development of the times marked by increasingly dynamic social, cultural, technological, and lifestyle changes. The background of the problem in this paper departs from the fact that the church often faces challenges in maintaining its theological identity while responding to the demands of the modern era, so that a contextual and relevant understanding of ecclesiology is needed. The research method used is a qualitative method with a library research approach, namely reviewing and analyzing various library sources such as the Bible, theological books, scientific journals, and church documents related to ecclesiology and the role of the church. The purpose of writing this article is to re-examine the nature of the church from a theological perspective and formulate the church's calling to remain faithful to God's mission amidst the changing times. The benefits of this paper are expected to provide theoretical contributions to the development of church theology studies and become material for practical reflection for the church in carrying out its duties of fellowship, service, witness, and diakonia in a relevant, contextual, and responsible manner in modern society.